2013
DOI: 10.1002/glia.22505
|View full text |Cite
|
Sign up to set email alerts
|

Polarized distribution of AMPA, but not GABAA, receptors in radial glia‐like cells of the adult dentate gyrus

Abstract: Glial fibrillary acidic protein (GFAP)-positive astrocytes with radial processes [radial glia (RG)-like cells] in the postnatal dentate gyrus share many of the characteristics of embryonic radial glia and appear to act as precursor cells for adult dentate neurogenesis, a process important for pattern separation and hippocampus-dependent learning. Although much work has delineated the mechanisms underlying activity-neurogenesis coupling via gamma-amino butyric acid (GABA)ergic neurotransmission on GFAP-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Supporting this notion, recent ultrastructural analysis demonstrated that the bushy processes of rNSCs wrap around glutamatergic synapses likely formed between MCs and mature GCs (Moss et al, 2016). Additionally, comparative recordings of patches from soma vs radial processes demonstrated that glutamatergic receptors are present in the radial processes (but not the soma) of the rNSCs (Renzel et al, 2013). Functionally, we identified a critical role of MC activity states in regulating rNSC quiescence.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, recent ultrastructural analysis demonstrated that the bushy processes of rNSCs wrap around glutamatergic synapses likely formed between MCs and mature GCs (Moss et al, 2016). Additionally, comparative recordings of patches from soma vs radial processes demonstrated that glutamatergic receptors are present in the radial processes (but not the soma) of the rNSCs (Renzel et al, 2013). Functionally, we identified a critical role of MC activity states in regulating rNSC quiescence.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study, however, suggests that type 1 cells also express GABA A receptors throughout and AMPA receptors only in their processes with no ionotropic glutamate receptors (Renzel et al 2013). Although type 1 cells can respond to extrinsic stimuli by increasing cell proliferation (Huttmann et al 2003;Kunze et al 2006;Weber et al 2013), the burden of expansion lies on the type 2 cells.…”
Section: The Precursor Cell Phasementioning
confidence: 99%
“…GABAergic receptors fall into two major groups, the ionotropic GABA-activated chloride channels that typically hyperpolarize neurons in the adult brain (Olsen and Sieghart 2008) and the metabotropic GABA B receptors that are coupled to G proteins and (when coupled with Gi/o proteins) reduce calcium and increase potassium conductance via voltage-gated calcium and inwardly rectifying potassium channels, respectively (Bowery et al 2002). Both types of receptors are expressed on embryonic and adult neural progenitors (Tozuka et al 2005; Renzel et al 2013; Giachino et al 2014). …”
Section: Neurotransmitter Signaling In Embryonic and Adult Neurogenesismentioning
confidence: 99%
“…In the adult SGZ, although proliferating cells express NMDAR1 and AMPA GluR2 subunits (Bekiari et al 2015), aNSCs were originally reported as responding to GABA but not to glutamate stimulation (Tozuka et al 2005). However, this apparent functional absence of responsiveness to glutamate may be because of the fact that receptor agonists were applied to the soma of aNSCs (Tozuka et al 2005) and not to their tufted processes that was only recently reported to harbor AMPA/kainate functional receptors (Renzel et al 2013). These receptors seem to be absent in aNSCs of the SEZ (Liu et al 2006), which correlates with are duction of the number of cells expressing NMDAR1, R2A, and R2B subunits from early postnatal age to adulthood (Fan et al 2012).…”
Section: Neurotransmitter Signaling In Embryonic and Adult Neurogenesismentioning
confidence: 99%